I have this language L = {a^n b^m c^k: m = |n - k|}
.
I know m = |n - k|
can be expressed in two ways
1) m = n - k for n >= k or n = m + k
2) m = k - n for k >= n or k = m + n
Therefore, I get two languages where
L1 = {a^n b^m c^k: n = m + k}
and
L2 = {a^n b^m c^k: k = m + n}
.
Then I claimed L
is the union of the two, L = L1 U L2
.
I don't quite understand how to generate a grammar where one exponent of a terminal is the summation of the other two terminals. i.e, in L1
you have n = m + k
.
Also L1
can be simplified further to
a^n => a^(m+k) => a^(m)a^(k)
so L1
becomes
L1 = {a^m a^k b^m c^k: m, k >= 0}
Attempt answer for
L1 = {a^m a^k b^m c^k: m, k >= 0}
A grammar G1
S -> A|B
A -> aAb|lambda
B -> aBc|lambda
For L1 you can do it with
and analogous for L2.